Analysis Of the Effect Of E-Accounting And E-Payroll on The Effectiveness Of Internal Control - Wibawa, Herry Wira; Ali, Hendry Muhammad; Permada, Dewi Nari Ratih; Yasin, Verdi (International Journal of Informatics, Economics, Management and Science; Vol 1 No 1 (2022): IJIEMS (January 2022), 2022)
Purpose of this study is to determine the effect of e- accounting and e- payroll on the effectiveness of internal control partially or simultaneously. The population of this study was 57 employees, and a sample of 57 people was assigned. The sampling technique was carried out by method sampling saturated or census. The data collection technique was carried out using a research instrument in the form of a questionnaire. The collected data was processed with the IBM Statistics SPSS application using the statistical method of multiple regression analysis. The results of this study indicate that partially there is a significant effect between e- accounting on the effectiveness of internal control and e- payroll on the effectiveness of internal control. Simultaneously there is an influence between e- accounting and e- payroll on the effectiveness of internal control . The independent variables, namely e-accounting and e-payroll, affect the dependent variable or the effectiveness of internal control by 92.5%, and 7.5% is influenced by other variables outside this study..